The Importance of Friendship for School-Age Children - Millie Ferrer; Anne M. Fugate (EDIS)
Parents can do a great deal to prepare their children to make friends by maintaining a warm relationship with them and being a good role model. This document discusses the ways parents can help prepare their children. This document is FCS2207, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, IFAS, Gainesville FL 32611. Published May 2003.